Hollow Engineering to Co@N‐Doped Carbon Nanocages via Synergistic Protecting‐Etching Strategy for Ultrahigh Microwave Absorption - Liu, Panbo; Gao, Sai; Zhang, Guozheng; Huang, Ying; You, Wenbin; Che, Renchao (Advanced functional materials, 2021)
Rational manipulation of hollow structure with uniform heterojunctions is evolving as an effective approach to meet the lightweight and high‐performance microwave absorption for metal‐organic frameworks (MOFs) derived absorbers. Herein, a new and controlled synergistic protecting‐etching strategy is proposed to construct shelled ZIF‐67 rhombic dodecahedral cages using tannic acid under theoretical guidance, then hollow Co@N‐doped carbon nanocages with uniform heterojunctions and hierarchical micro‐meso‐macropores are obtained via a pyrolysis process, which addresses the shortcomings of using sacrificing templates or corrosive agents. The outer Co@N‐doped carbon shell, composed of highly dispersive core‐shell heterojunctions, possesses micro‐mesopores while the inner hollow macroporous cavity endows the absorbers with lightweight characteristics. Accordingly, the maximum reflection loss is −60.6 dB at 2.4 mm and the absorption bandwidth reaches 5.1 GHz at 1.9 mm with 10 wt% filler loading, exhibiting superior specific reflection loss compared with the vast majority of previous MOFs derived absorbers. Furthermore, this synergistic protecting‐etching strategy provides inspiration for precisely creating a hollow void inside other MOFs crystals and broadens the desirable candidates for lightweight and high‐efficient microwave absorbers. In this manuscript, a new and controlled synergistic protecting‐etching strategy to construct shelled ZIF‐67 cages is proposed, which addresses the shortcomings of conventional strategies for hollow engineering. The synthesized shelled cages are then converted into hollow Co@N‐doped carbon nanocages with uniform heterojunctions and hierarchical micro‐meso‐macropores via a pyrolysis process.